PENGEMBANGAN E-LIBRARY DALAM MENINGKATKAN PELAYANAN DI PERPUSTAKAAN IAIN BATUSANGKAR - Tri Yuliani (IAIN Batusangkar, 2017)
Information and communication technology is the most important part of IAIN Batusangkar library. The development of e-library or digital library in IAIN Batusangkar library is a solution to overcome various phenomena such as individual phenomenon, the distance location, social environment demanding fast and accurate information needs without having to visit the library and data collection requirement that can be accessed at any time. Responding to this phenomenon, IAIN Batusangkar Library developed a computerized automation system directed to improve the service process to the user library with good quality and speed, as well as to improve the effectiveness and efficiency of library management. The approach used is internet-based visualization. Digital Library is built by using Zi-shof e-library application of e-campus model. In the Digital Library is available a variety of collection of books, theses, journals, and research reports. The development of E-Library can be accessed either by students or not through the campus application of IAIN Batusangkar with the access library port http: //pustaka.iainbatusangkar. It answered a challenge and an important goal for an institution to develope the library in the future.